COLLABORATIVE GOVERNANCE DALAM PENGEMBANGAN KONSERVASI MANGROVE BAROS DI DESA TIRTOHARGO KECAMATAN KRETEK KABUPATEN BANTUL - Devi Arianti; lena Satlita (NATAPRAJA, 2018)
This study aimed to know and deeply understand the Collaborative Governance processin the development of Baros's Mangrove Conservation and its inhibiting factors. The research design used was descriptive with qualitative approach. The resultsof this study indicated that Collaborative Governance process in the development of Baros'sMangrove Conservation that was done with the concept of agro silvo fishery had been done bygovernment, private, and community. However, the Collaborative Governance processhad not been optimally implemented, it could be seen from the inhibiting factors that occuredthat were: there was no communication forum, there was still sectoral ego, the limitedresources, and the private involvement was less than the maximum.